Preparação de carvão ativado a partir de torta prensada de Raphanus sativus L. e utilização para clarificação de soluções. - Diego Luiz Nunes (2009)
The search for healthier food products has favored research and processes that employ lower amounts of chemical substances in the production chain, so the final products can be termed eco-friendly. Sugar is an extensively used food product and its production involves a wide variety of chemical reagents that are needed in order to obtain a finalproduct without color and with controlled size. The present study has the objective of developing an adsorbent, based on an agri-industrial residue (potential poluting agent), the pressed cake obtained after pressing Raphanus sativus L. seeds for oil extraction, which presents interest for biodiesel production. With the objective of improving its adsorptivepotential, the Raphanus sativus L. pressed cake was submitted to carbonization in a microwave oven, as a lower energy consumption alternative for the production of an activated carbon. Several processing times were evaluated in order to establish the carbonization procedure. The adsorption potential was evaluated for methylene blue removal from aqueous solutions. Experiment design was employed in order to verify the best combination of the following parameters: initial dye concentration, initial solution pH, particle diameter and the ratio between the amount of adsorbent and adsorbate. All parameters were considered relevant (p . 5%). The adsorption process was studied withrespect to mathematical models that allowed for its characterization in terms of equilibrium, kinetics and thermodynamics. The models that provided the best fits with respect to equilibrium and kinetics data were Langmuir and pseudo second-order (type I), respectively. From a thermodynamics point of view, the process was found to beexpontaneous and favorable, with a small variation of internal energy. After evaluation of the adsorption process, the adsorbent was employed for brown sugar clarification (aqueous solution). The produced adsorbent provided approximately 30% of color removal. Chemical activation was tested, which provided 80% clarification of the brownsugar aqueous solution. Such results demonstrated the potential of agricultural residues in the production of adsorbents with application in food processing